GENETIC STUDIES OF FIBER QUALITY CHARACTERS IN UPLAND COTTON - A. Hussain; F. M. Azhar M. A. Ali; S. Ahmad; K. Mahmood Cotton Research Station; Vehari; Pakistan (Journal of Animal and Plant Sciences, 2010)
Five upland cotton cultivars were crossed in a complete diallel crossing system to investigate inheritance pattern and combining ability of parents for different fiber quality traits like staple length, fiber strength, fineness and uniformity. The study was carried out in the Department of Plant Breeding and Genetics, University of Agriculture, Faisalabad during the years 2005-07.  Highly significant differences were found among the genotypes for all the traits under study. Genetic analysis of the data also revealed highly significant effects due to general as well as specific combining ability (P ≤ 0.01) for all the fiber quality characters. The magnitude of variance due to dominance was greater than that of additive effects for all the traits which showed that these traits were controlled by non-additive gene action. The parent CIM-707 showed best general combining ability for staple length and fiber strength, FH-1000 for fiber fineness and LA-17801 for fiber uniformity. The best specific combining ability was shown by the cross CIM-707 x DPL-2775 for staple length, CIM-707 x LA-17801 for fiber strength, FH-1000 x DPL-2775 for fiber fineness and CIM-707 x TH-41/83 for fiber uniformity. Correlation analysis demonstrated positive association between fiber strength and staple length while fiber fineness displayed negative relationship with staple length and fiber strength. Therefore, genetic information acquired from this study offer opportunities for cotton breeders to intensify the rapid improvement for the fiber quality traits in cotton crop while utilizing the genetic resources.
Keywords: cotton; fiber quality; combing ability; gene action; correlation